2013
DOI: 10.22270/jddt.v3i3.498
|View full text |Cite
|
Sign up to set email alerts
|

Stability Indicating Liquid Chromatographic Method for the Quantitative Determination of Valganciclovir in Pharmaceutical Dosage Forms

Abstract: A selective, specific and sensitive stability-indicating high-performance liquid chromatographic method was developed and validated for the determination of Valganciclovir in tablet dosage forms. Reversed-phase chromatography was performed on Shimadzu Model CBM-20A/20 Alite, equipped with SPD M20A prominence photodiode array detector (Isocratic mode) using C18 column (250 mm × 4.6 mm, 5 μm) with a flow rate of 0.8 mL/min. UV detection was carried at 254 nm. Linearity was observed in the concentration range of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 6 publications
(5 reference statements)
0
3
0
Order By: Relevance
“…After then, it was converted to its triphosphate form by cellular kinases. 2 According to a review of the valganciclovir literature, UV methods, [1][2][3] LC-MS methods [4][5][6][7][8] and RP-HPLC methods [9][10][11][12][13] were published up to this point. The study's major objective was to create an easy, precise RP-HPLC method for the measurement of valganciclovir in both pure and tablet dose forms.…”
Section: Introductionmentioning
confidence: 99%
“…After then, it was converted to its triphosphate form by cellular kinases. 2 According to a review of the valganciclovir literature, UV methods, [1][2][3] LC-MS methods [4][5][6][7][8] and RP-HPLC methods [9][10][11][12][13] were published up to this point. The study's major objective was to create an easy, precise RP-HPLC method for the measurement of valganciclovir in both pure and tablet dose forms.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6] . Literature Survey revealed that the drug has been estimated by UV-Spectrophotomtric [11][12][13] , RP-HPLC [14][15][16][17] , HPTLC [18] and Liquid chromatographic method [19][20][21] has been reported so far. The present study describes a simple, precise and accurate analytical method for the estimation of Valganciclovir hydrochloride in bulk and pharmaceutical dosage forms.…”
Section: Introductionmentioning
confidence: 99%
“…In cytomegalovirus infected cells, ganciclovir is initially phosphorylated to the monophosphate form by viral protein kinase and then it is further phosphorylated via cellular kinases to produce the triphosphate form. 1 Very few methods are reported in the literature including liquid chromato graphic methods, [2][3][4] spectrophotometric techniques 5 and LC/ MS/MS [6][7][8] methods for the determination of Valganciclovir in tablet dosage forms As there was no work in the literature about the UV spectrophotometric method for the analysis of VGC using method a, b, c and d by zero order and first order derivative. Therefore, the objective of present study was to develop and validate a simple, precise, accurate and economical UV spectrophotometric method for estimation of VGC.…”
Section: Introductionmentioning
confidence: 99%